2020
DOI: 10.1111/are.14867
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharide supplementation in diets for tropical gar ( Atractosteus tropicus ) juvenile: Effects on morphophysiology and intestinal barrier function

Abstract: Supplementary fructooligosaccharides (FOS) were evaluated on growth, survival, gut morphology, digestive enzyme activity and expression of intestinal barrier genes in tropical gar (Atractosteus tropicus). Four treatments were designed to include FOS (5, 10, 15 and 20 g/Kg) and were compared with a control (0 g/Kg) and the current commercial trout diet. Ten fish were stocked (0.25 ± 0.01 g and 4.2 ± 0.4 cm total length) per experimental unit by triplicate in a 45-day experiment. Fish fed with 5 and 10 g/Kg of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 73 publications
4
2
0
Order By: Relevance
“…While acid protease activity was greater in fish fed with 2.5 g kg −1 FOS, chymotrypsin and lipase activities were higher in the control diet. Similar to these results, previous work with A. tropicus juveniles showed that fish fed with 5 g kg −1 FOS showed higher acid protease activities [13]. Acid proteases are more abundant in the stomach of carnivorous fish species [33].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…While acid protease activity was greater in fish fed with 2.5 g kg −1 FOS, chymotrypsin and lipase activities were higher in the control diet. Similar to these results, previous work with A. tropicus juveniles showed that fish fed with 5 g kg −1 FOS showed higher acid protease activities [13]. Acid proteases are more abundant in the stomach of carnivorous fish species [33].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we evaluated the expression of the mucus layer protein MUC-2. Our results showed that muc-2 relative expression was up-regulated in A. tropicus larvae fed with 7.5 g kg −1 FOS, according to [13], who reported that A. tropicus juveniles fed 10 and 15 g kg −1 FOS showed overexpression of muc-2. While [24] did not show any differences in the muc-2 expression with the supplementation of β-glucans in juveniles of A. tropicus.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These results may be due to the action of organic acid salts which reduces pH in the stomach and intestine (Lee et al, 2015). Other studies in A. tropicus show increased activity of alkaline proteases, trypsin and chymotrypsin in sh fed with low concentrations of MOS and FOS (0 and 0.5%) (Nájera-Arzola et al, 2018; Sepúlveda-Quiroz et al, 2021). The activity of lipases and amylases were not modi ed between treatments, similar to the results reported by Nieves-Rodríguez et al ( 2018) when including B-glucans in diets for juveniles of A. tropicus.…”
Section: Discussionsupporting
confidence: 82%